Clinical pharmacokinetics and outcomes of oral fluconazole therapy in dogs and cats with naturally occurring fungal disease. Issue 6 (12th July 2020) - KuKanich, Kate; KuKanich, Butch; Lin, Zhoumeng; Rankin, Amy J.; Hanzlicek, Andrew S.; Palerme, Jean‐Sebastien; Bach, Jonathan; Cook, Audrey K.; Juracek, Amy; Joo, Hyun
Abstract: This multi‐institutional study was designed to determine the clinical pharmacokinetics of fluconazole and outcomes in client‐owned dogs ( n  = 37) and cats ( n  = 35) with fungal disease. Fluconazole serum concentrations were measured. Pharmacokinetic analysis was limited to animals at steady state (≥72 hr of treatment). The mean (range) body weight in 31 dogs was 25.6 (2.8–58.2) kg and in 31 cats was 3.9 (2.4–6.1) kg included in pharmacokinetic analyses. The dose, average steady‐state serum concentrations (CSS ), and oral clearance in dogs were 14.2 (4.5–21.3) mg/kg/d, 26.8 (3.8–61.5) µg/mL, and 0.63 ml min −1  kg −1, respectively, and in cats were 18.6 (8.2–40.0) mg/kg/d, 32.1 (1.9–103.5) µg/mL, and 0.61 ml min −1  kg −1, respectively. Random inter‐animal pharmacokinetic variability was high in both species. Two dogs had near twofold increases in serum fluconazole when generic formulations were changed, suggesting lack of bioequivalence. Median CSS for dogs and cats achieving clinical remission was 19.4 and 35.8 µg/ml, respectively. Starting oral doses of 10 mg/kg q12h in dogs and 50–100 mg total daily dose in cats are recommended to achieve median CSS associated with clinical remission. Due to the large pharmacokinetic variability, individualized dose adjustments based on CSS (therapeutic drug monitoring) and treatment failure should be considered.